Jolanta Sławek, Poetyckie żywioły sacrum. obrazy świętości w utworach Janusza Stanisława Pasierba, Karola Wojtyły / Jana Pawła II, Anny Kamieńskiej i Zbigniewa Jankowskiego, Poznań: Wydawnictwo Naukowe UAM, 2018, 298 s. - Nowak, Małgorzata (Stylistyka, 2019)
Artykuł recenzyjny